Legal Protection For The People Of Buleleng Regency In Providing Smoking-Free Area Services Based On Buleleng Regional Regulation Number 2 Of 2015 Concerning Non-Smoking Areas - Mangku, Dewa Gede Sudika (Universitas Muhammadiyah Surabaya, 2022)
This study aims to determine the legal protection for the people of Buleleng Regency in providing smoke-free area services based on Buleleng Regency Regulation Number 2 of 2015 concerning Non-Smoking Areas. In this study, the type of research used is normative legal research by using legal material collection techniques in the form of document studies or literature studies. The approach used in this research is a statutory approach and the sources of legal materials used are primary legal materials, secondary materials, and tertiary legal materials. The results of the study show that the Buleleng Regency Regulation Number 2 of 2015 concerning Non-Smoking Areas has provided legal protection to the community by establishing a smoke-free area, regulating obligations and prohibitions related to non-smoking areas and regulating administrative and criminal sanctions for parties who do not violate no smoking area regulations. So based on this, it is hoped that legal protection for the people of Buleleng Regency in providing smoke-free area services can be fulfilled.Keywords: legal protection, no smoking area, Buleleng Regency